Pyrocardan Trapeziometacarpal Joint Arthroplasty—Medium-Term Outcomes - Logan, James; Peters, Susan E.; Strauss, Ruby; Manzanero, Silvia; Couzens, Gregory B.; Ross, Mark (Journal of Wrist Surgery, 2020)
Objective Pyrocardan trapeziometacarpal interposition implant is a free intra-articular spacer composed of pyrocarbon. This biconcave resurfacing implant, both ligament and bone-stock sparing, is indicated for use in early-to-moderate stage trapeziometacarpal osteoarthritis. It was hypothesized that the postoperative outcome measures of the Pyrocardan implant would be comparable to those seen with ligament reconstruction and tendon interposition (LRTI) surgeries and those reported by the designer of the implant, Phillipe Bellemère, but that strength would be greater than for LRTI.Methods In this prospective case series, 40 Pyrocardan implants were performed in 37 patients. Average age was 58 years (range: 46–71). Patients were assessed preoperatively, 3 months, 6 months, 1 year, 2 years, and beyond (long term) wherever possible.Results There have been no major complications or revision surgeries for the series. Average follow-up was 29 months (range: 12 months–7 years). Twenty-eight joints were assessed at over 2 years post index surgery. Outcome measure scores improved from preoperative assessment to the most recent follow-up equal or greater than 2 years. Average grip strength at 2 years was 30 kg, as compared with 19.6 kg in an age-matched cohort who underwent trapeziectomy and 25 kg in Bellemère's original series of Pyrocardan implants.Conclusions Pyrocardan interposition arthroplasty appears to be a safe, effective treatment for trapeziometacarpal arthritis. Patient-reported clinical outcomes were at least equivalent to LRTI and are comparable to Bellemère's original series. Grip and pinch strength appear to be better than LRTI.Level of Evidence This is a Level III, prospective observational cohort study.
Keywords: thumb; trapeziometacarpal joint; pyrocarbon; total joint arthroplasty